Religion and Economic Development: Past, Present, and Future - Sascha O. Becker; Amma Panin; Steven Pfaff; Jared Rubin (Institute of Labor Economics (IZA), 2025)
This chapter examines the role of religion in economic development, both historically and today. Religion's influence varies globally, with high religiosity in countries like Pakistan and low rates in China. Despite declines in some Western countries, religion remains influential worldwide, with projected growth in Muslim populations due to higher fertility rates. Religion continues to shape societal norms and institutions, such as education and politics, even after its direct influence fades. The chapter explores how religious institutions and norms have impacted economic outcomes, focusing on both persistence and decline. It also examines cultural transmission, institutional entrenchment, networks, and religious competition as mechanisms sustaining religion's influence. We explore the relationship between religion and secularization, showing that economic development does not always reduce religiosity. Lastly, the chapter highlights gaps in the literature and suggests future research areas on the evolving role of religion in economic development.
Keywords: D85; I25; J10; N30; O33; O43; P48; Z10; Z12; 330; networks; economic development; religiosity; cultural transmission; secularization; historical persistence; religion; religious competition; social norms